Bridges an introduction to ten great bridges and their designers - Cornille, Didier 1951- (Who built that?, 2016)
"In Who Built That? Bridges, illustrator Didier Cornille presents ten of the most important bridges in the world, from the world's first cast-iron bridge (The Iron Bridge) to the longest pre-stressed concrete bridge in the southern hemisphere (The Rio-Niteroi Bridge) to the tallest bridge in the world (the Millau Viduct). Introducing each engineer or architect, the main concepts of their work, as well as some of their most important projects in charming drawings and accessible text, Bridges is a fun primer for anyone interested in learning more about these incredible structures. Didier's step-by-step drawings of bridges ranging from the Brooklyn Bridge (1883) and the Sydney Harbour Bridge (1932) to Santiago Calatrava's Peace Bridge (2012) and Rudy Ricciotti's MUCEM Footbridge (2013), provide original insight into the development of the engineering and architectural concepts behind each bridge"...